2020
DOI: 10.3892/etm.2020.8411
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum 25‑OH vitamin D expression and non‑alcoholic fatty liver disease

Abstract: This study investigated changes in the level of serum 25(OH)D] in patients with non-alcoholic fatty liver disease (NAFLD) and the correlation between the severity of NAFLD and 25(OH)D. A retrospective analysis was performed on 385 NAFLD patients (NAFLD group) admitted to the Zhongshan Hospital and 347 healthy people with physical examination (control group). The height and weight of all subjects were measured, and BMI was calculated. Fasting venous blood was extracted for the determination of blood glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…More and more studies had shown that the low levels of vitamin D were closely related to the occurrence and development of NAFLD [ 13 , 25 , 26 ]. Lai et al [ 27 ] found that compared with healthy control group, the levels of 25-(OH) D were significantly lower in NAFLD patients,especially in patients with moderate and severe NAFLD. Yang et al [ 13 ] also found that serum 25-(OH) D decreased significantly in patients with liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies had shown that the low levels of vitamin D were closely related to the occurrence and development of NAFLD [ 13 , 25 , 26 ]. Lai et al [ 27 ] found that compared with healthy control group, the levels of 25-(OH) D were significantly lower in NAFLD patients,especially in patients with moderate and severe NAFLD. Yang et al [ 13 ] also found that serum 25-(OH) D decreased significantly in patients with liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glycosylated hemoglobin type A1C was found not to be significantly associated with the presence of NAFLD. A previous study from China has reported that glycosylated hemoglobin level is not significantly different between healthy and mild NAFLD groups, but it significantly increased in moderate and severe NAFLD groups, suggesting that the glycosylated hemoglobin is still important in terms of NAFLD and needs to be considered especially when evaluating the severity of NAFLD (27).…”
Section: Discussionmentioning
confidence: 93%
“…More and more studies had shown that the low levels of vitamin D were closely related to the occurrence and development of NAFLD [12,24,25].Lai et al [26] found that compared with healthy control group, the levels of 25-(OH)D were signi cantly lower in NAFLD patients,especially in patients with moderate and severe NAFLD. Yang et al [12] also found that serum 25-(OH)D decreased signi cantly in patients with liver brosis.…”
Section: Discussionmentioning
confidence: 99%